Association Between Polymorphisms of Metabolic Enzyme Genes and Chromosomal Damage in Benzene-Exposed Workers in China. Issue 11 (November 2017) - Fang, Yan; Wu, Han-Tian; Ye, Yun-Jie; Zhou, Li-Fang; Hu, Wei; Zhang, Guang-Hui; Sun, Pin; Au, William; Xia, Zhao-Lin
Abstract : Objective: To provide better understanding of genetic susceptibility for health risk among current benzene-exposed workers. Methods: Four hundred sixty one benzene-exposed workers and 88 matched controls were recruited, and their benzene exposure doses were monitored. Associations between genetic susceptibility for polymorphisms of metabolic enzymes CYP2E1 and NQO1, and expression of cytokinesis-block micronucleus (MN) were investigated. Results: Mean MN frequency in the exposed workers was significantly higher than that in the control group ( P < 0.01). Individuals with the NQO1 609 CC genotype showed significantly higher MN frequencies than those with the TT genotype ( P < 0.05) in either single- or multiple-factor analyses. Age was an effect modifier for elevated MN frequency, while sex, smoking, and alcohol consumption had no relationship. Conclusion: Exposure to low dose of benzene among current workers can still cause health risk, especially among those with the NQO1 609 CC genotype.